2017
DOI: 10.1016/j.neuropharm.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of recombinant Netrin-1 attenuates neuronal apoptosis by activating DCC/APPL-1/AKT signaling pathway after subarachnoid hemorrhage in rats

Abstract: Neuronal apoptosis is a crucial pathological process in early brain injury after subarachnoid hemorrhage (SAH). The effective therapeutic strategies to ameliorate neuronal apoptosis are still absent. We intended to determine whether intranasal administration of exogenous Netrin-1 (NTN-1) could attenuate neuronal apoptosis after experimental SAH, specifically via activating DCC-dependent APPL-1/AKT signaling cascade. Two hundred twenty-five male Sprague-Dawley rats were subjected to the endovascular perforation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Innate immune responses and inflammation contribute to the pathophysiology of EBI following SAH (Xie et al, 2017 ). In this study, we investigated the role of PP2A and TTP in EBI after SAH and found that silencing PP2A or TTP exacerbated brain edema and reduced neurological scores following SAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune responses and inflammation contribute to the pathophysiology of EBI following SAH (Xie et al, 2017 ). In this study, we investigated the role of PP2A and TTP in EBI after SAH and found that silencing PP2A or TTP exacerbated brain edema and reduced neurological scores following SAH.…”
Section: Discussionmentioning
confidence: 99%
“…The rat model of SAH was generated as previously described (Xie et al, 2017 ), with some modifications. Briefly, animals were anesthetized with 3% isoflurane in 60/40% medical air/oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…Double fluorescence staining was conducted as described previously [ 27 ]. The rats were deeply anesthetized at 24 h post-SAH and were transcardially perfused with 60-ml ice-cold PBS followed by 60 ml of 10% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, NT-1 phosphorylated AMP-activated protein kinase (AMPK) and reduced the phosphorylation of mammalian target of rapamycin (mTOR) and P70S6K in a spinal cord injury model [ 36 ]. NT-1 also activated APPL1-AKT signing pathway via combining with DCC receptor to reduce apoptosis after subarachnoid hemorrhage in rats [ 37 ]. When introducing to astrocytes, AKT signing pathway was reported to protect astrocytes from activation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%